Genomic Survey of E. coli From the Bladders of Women With and Without Lower Urinary Tract Symptoms - Garretto, Andrea; Miller-Ensminger, Taylor; Ene, Adriana; Merchant, Zubia; Shah, Aashaka; Gerodias, Athina; Biancofiori, Anthony; Canchola, Stacey; Canchola, Stephanie; Castillo, Emanuel; Chowdhury, Tasnim; Gandhi, Nikita; et al. (Frontiers in Microbiology, 2020)
Urinary tract infections (UTIs) are one of the most common human bacterial infections. While UTIs are commonly associated with colonization by Escherichia coli, members of this species also have been found within the bladder of individuals with no lower urinary tract symptoms, also known as asymptomatic bacteriuria. Prior studies have found that both uropathogenic E. coli (UPEC) strains and E. coli isolates that are not associated with UTIs encode for virulence factors. Thus, the reason(s) why E. coli sometimes causes UTI-like symptoms remain(s) elusive. In this study, the genomes of 66 E. coli isolates from adult female bladders were sequenced. These isolates were collected from four cohorts, including women: (1) without lower urinary tract symptoms, (2) overactive bladder symptoms, (3) urgency urinary incontinence, and (4) a clinical diagnosis of UTI. Comparative genomic analyses were conducted, including core and accessory genome analyses, virulence and motility gene analyses, and antibiotic resistance prediction and testing. We found that the genomic content of these 66 E. coli isolates does not correspond with the participant’s symptom status. We thus looked beyond the E. coli genomes to the composition of the entire urobiome and found that the presence of E. coli alone was not sufficient to distinguish between the urobiomes of individuals with UTI and those with no lower urinary tract symptoms. Because E. coli presence, abundance, and genomic content appear to be weak predictors of UTI status, we hypothesize that UTI symptoms associated with detection of E. coli are more likely the result of urobiome composition.